READING SURAH YASIN AT NIGHT: Study of Takhrij al-Hadits - Asrar Mabrur Faza (Jurnal Ushuluddin, 2016)
Based on Hadith which is still debatable, we are suggested to read certain Surah in al- Qur’an, such as reading of Surah Yasin at night, But, it is still needed to re-clarified to see the source or quality. The study of Takhrij hadith is a means to conduct those clarified. Search resources of Hadith code about reading Surah Yasin at night is done by using one of Takhrij methods. Searching the quality of hadith is done by analysis of rijal (criticism of sanad) and analysis of material (criticism of matan). Thus, it can be obtained that hadith of reading surah Yasin is more listed outside al-kutub al-tis’ah, as well as weak, both in the aspect of sanad and matan